Impact and Limitations of the 2015 National Health and Safety Network Case Definition on Catheter-Associated Urinary Tract Infection Rates. (24th November 2016) - Bardossy, Ana Cecilia; Jayaprakash, Rachna; Alangaden, Anjali C.; Starr, Patricia; Abreu-Lanfranco, Odaliz; Reyes, Katherine; Zervos, Marcus J.; Alangaden, George J.
Abstract : Application of the new 2015 NHSN definition of catheter-associated urinary tract infection (CAUTI) in intensive care units reduced CAUTI rates by 50%, primarily due to exclusion of candiduria. This significant reduction in CAUTI rates resulting from the changes in the definition must be considered when evaluating effectiveness of CAUTI prevention programs. Infect Control Hosp Epidemiol 2017;38:239–241